Nonlinear observation in fuel cell systems: A comparison between disturbance estimation and High-Order Sliding-Mode techniques - Luna, Julio; Usai, Elio; Husar, Attila; Serra, Maria (International journal of hydrogen energy, 2016)
This paper compares two Nonlinear Distributed Parameter Observers (NDPO) for the observation of a Proton Exchange Membrane Fuel Cell (PEMFC). Both NDPOs are based on the discretisation of distributed parameters models and they are used to estimate the state profile of gas concentrations in the anode and cathode gas channels of the PEMFC, giving detailed information about the internal conditions of the system. The reaction and water transport flow rates from the membrane to the channels are uncertainties of the observation problem and they are estimated throughout all the length of the PEMFC without the use of additional sensors. The first observation approach is a Nonlinear Disturbance Observer (NDOB) for the estimation of the disturbances in the NDPO. In the second approach, a novel implementation of a High-Order Sliding-Mode (HOSM) observer is developed to estimate the true value of the states as well as the reaction terms. The proposed observers are tested and compared through a simulation example at different operating points and their performance and robustness is analysed over a given case study, the New European Driving Cycle. •We model an PEMFC to estimate the internal concentrations.•Two nonlinear distributed parameters observers are designed.•The observers estimate the reaction and water transport terms of the PEMFC.•Novel design of a HOSM observer.•The designed observers are able to estimate the internal conditions of the PEMFC.